The Influence Of Job Characteristics On Organizational Citizenship Behaviour And Job Engagement And Its Implications For Employee Performance - Sarah Ladita; Survival Survival; Choirul Anam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyse the influence of job characteristics on Organizational Citizenship Behaviour and Job Engagement, and its implications for employee performance. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 78 employees from the Faculty of Social and Political Sciences, Universitas Brawijaya. Data analysis was conducted using path analysis techniques with the Smart-PLS3 tool to test the relationship between the variables studied. The results showed that job characteristics are not significant to employee performance. Furthermore, job characteristics have a significant effect on OCB. Meanwhile, OCB has a significant effect on employee performance. In addition, it was found that job characteristics have a significant effect on job engagement. Then, job engagement has a significant effect on employee performance. The OCB variable has a role as mediation. Meanwhile, the job engagement variable is not significant as a mediation. This research provides insight for HR practitioners in designing jobs that can maximise employee potential.